Analysis of the Influence of Medical Personnel Competence and Service Quality on Patient Satisfaction and Its Implications on Patient Loyalty - Putra , Muhammad David Perdana; Djogo, Y Ony; Rulia, Rulia (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to analyze the influence of medical personnel competence and service quality on patient satisfaction and its implications on patient loyalty at Muhammadiyah Babat Hospital. Medical personnel competence and service quality are two key factors that determine the level of patient satisfaction, which in turn can affect patient loyalty. The research method used is quantitative with a survey approach. Data were collected through questionnaires distributed to patients of Muhammadiyah Babat Hospital. The sample of this study consisted of 134 respondents selected randomly. Data analysis was conducted using path analysis to determine the effect of independent variables (medical personnel competence and service quality) on the dependent variable (patient satisfaction) and to evaluate the implications for patient loyalty. The results of the study indicate that the competence of medical personnel and service quality have a positive and significant influence partially and simultaneously on patient satisfaction. Patient satisfaction has a strong influence on patient loyalty. This finding indicates that in order to improve patient satisfaction and loyalty, Muhammadiyah Babat Hospital needs to focus on improving the competence of medical personnel through continuous training and development and ensuring consistent service quality that meets patient expectations. Thus, the hospital can build a good reputation and maintain a loyal patient base. This study provides an important contribution to hospital management in developing strategies to improve service quality and more effective human resource management. In addition, this study can also be a reference for further studies in the field of hospital management and health services.